Legal Responsibility of Medical Personnel in Cases of Malpractice in Telemedicine - Yohanes Firmansyah; Putri Mahirah Afladhanti (LITERACY : International Scientific Journals of Social, Education, Humanities, 2025)
The COVID-19 pandemic has accelerated the adoption of telemedicine in Indonesia as a cross-regional alternative to conventional healthcare services. This technology-based medical practice offers increased accessibility and efficiency, yet it also presents legal challenges, particularly concerning physicians' liability in malpractice cases. This study aims to examine the legal responsibility of physicians in post-pandemic telemedicine using a normative juridical approach. It analyzes six key areas: the innovation and legal challenges of telemedicine; the concept of malpractice and legal liability; regulatory dynamics in Indonesia; malpractice risks in virtual practice; international legal comparisons (United States, United Kingdom, Singapore); and recommendations for legal reform. The method used was a normative legal study with statute and comparative approaches. The secondary data used consists of primary legal materials (laws and regulations), secondary sources (academic literature), and tertiary materials (dictionaries/encyclopedias). The data was then systematically reviewed with a descriptive-analytical approach. The findings indicate that although Law No. 17 of 2023 and Government Regulation No. 28 of 2024 recognize telemedicine practice, technical regulations have led to legal uncertainty for patients and physicians. In contrast, other countries have already established legal frameworks that emphasize doctors' responsibilities in virtual care as equivalent to those in in-person settings. In conclusion, Indonesia must successfully formulate implementing regulations governing service standards, digital informed consent, complaint mechanisms, and the delineation of responsibilities between medical practitioners and platform providers. Such legal reform is essential to ensure that telemedicine evolves as an innovation aligned with patient rights protection and the principles of legal justice.